Usage of interactions among plants and pests in biogardens - Veress, Éva (Acta Agraria Debreceniensis, 2010)
Experiences has been gained in the last 25 years with plant extracts, fermented juices, infusions and brews of plant origin presented in present paper. Interactions among vegetables growing in mixed cultures have been also summarized with special regard to insect repellent plants and to those interaction when the target plant’s odour is covered and the pest cannot find it. These methods – after the ecological balance of the garden has been returned – can help the growers to keep the pest density under the economic threshold. The allelopathy can be the basis of the presented results.